Ascertainment and severity of Marfan syndrome in a Scottish population. Issue 1 (January 1994) - Gray, J R; Bridges, A B; Faed, M J; Pringle, T; Baines, P; Dean, J; Boxer, M
Abstract : This study in north east Scotland has shown that Marfan syndrome has a minimal birth incidence of 1:9802 live births, a minimal prevalence of 1:14217, and that 8/30 (26.7%) of cases in our series are new mutations. The calculated mutation rate is 15 +/- 6.7 x 10(-6) and there is evidence of reduced reproductive fitness.